Quasi-continuity on Product Spaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this present paper, the notion of Quasi-continuity on a product space is introduced.  The set of all such bounded Quasi-continuous functions defined on a closed and bounded interval is established to be a commutative Banach algebra under supremum norm.